Integrating Sustainability Accounting into Vocational Higher Education: A Bibliometric and Systematic Literature - Santoso Tri Hananto; Bambang Sutopo (Universitas Tidar, 2025)
This​‍​‌‍​‍‌​‍​‌‍​‍‌ research intends to map and critically evaluate worldwide research trends on the integration of sustainability accounting in the Vocational Higher Education (VHE) sector over the 2016–2025 period through combining bibliometric analysis and a systematic literature review (SLR). The bibliometric data were collected from the Scopus database. 90 peer-reviewed journal articles were identified and analyzed using VOSviewer. The research results show a marked rise in the number of publications post-2020, indicating the intensification of the issue of greening vocational education for the development of green skills and sustainability alignment agendas. The keyword co-occurrence analysis points to the existence of five main topical clusters: pedagogical transformation, sustainability and Education for Sustainable Development (ESD) frameworks, human development, environmental education policy, and digitalization and innovation in TVET. The SLR of 15 articles reveals that current research mainly makes use of Human Capital Theory, Institutional Theory, and Transformative Learning Theory as explanatory frameworks of the green human capital creation role of vocational education. Still, the literature is mostly theoretical and qualitative, hardly offering much empirical data to directly support the links between integrating sustainability accounting and learning outcomes, competency transfer, and labor-market relevance. Overall, this study contributes to accounting education for sustainability by providing a comprehensive mapping of the research landscape and identifying persistent gaps between policy intentions, curriculum implementation, and measurable outcomes. The findings offer practical insights for policymakers, vocational institutions, and professional bodies in developing sustainability-oriented accounting curricula aligned with SDG-driven workforce needs.